2004
DOI: 10.4049/jimmunol.172.10.6362
|View full text |Cite
|
Sign up to set email alerts
|

The Transmembrane CXC-Chemokine Ligand 16 Is Induced by IFN-γ and TNF-α and Shed by the Activity of the Disintegrin-Like Metalloproteinase ADAM10

Abstract: The novel CXC-chemokine ligand 16 (CXCL16) functions as transmembrane adhesion molecule on the surface of APCs and as a soluble chemoattractant for activated T cells. In this study, we elucidate the mechanism responsible for the conversion of the transmembrane molecule into a soluble chemokine and provide evidence for the expression and shedding of CXCL16 by fibroblasts and vascular cells. By transfection of human and murine CXCL16 in different cell lines, we show that soluble CXCL16 is constitutively generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
344
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 377 publications
(360 citation statements)
references
References 31 publications
14
344
2
Order By: Relevance
“…We and others have found that ADAM10 is responsible for most of the constitutive shedding, but not for the PMA-induced cleavage of CXCL16 (15,36). A role of ADAM17 in the latter process has been suggested by inhibitor studies (15), but needs to be confirmed by ADAM17-deficient cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We and others have found that ADAM10 is responsible for most of the constitutive shedding, but not for the PMA-induced cleavage of CXCL16 (15,36). A role of ADAM17 in the latter process has been suggested by inhibitor studies (15), but needs to be confirmed by ADAM17-deficient cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…The antiserum against CX3CL1 was raised in rabbits and characterized previously (39). Expression vectors for human CX3CL1 and CXCL16 cDNA were described before (15,34). For detection of C-terminal cleavage fragments (CTFs) of CX3CL1, a 2Z-tag (40) was fused to the C terminus of CX3CL1.…”
Section: Cytokines Abs Enzymes Inhibitors and Vectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…1D). Since the action of endogenous metalloproteinases may facilitate the release of soluble CXCL16 into the tissue culture supernatant [4,5], chemotaxis of CXCR6-transfected L1.2 cells to varying dilutions of culture media was assayed (Fig. 1E).…”
Section: Cxcr6 Transfectants Bind and Migrate In Response To Soluble mentioning
confidence: 99%
“…Although typically produced as soluble, secreted proteins, the chemokine CXCL16 also exists as a membrane-bound form, consisting of a chemokine domain, a mucin-type stalk, a single-pass transmembrane (TM) domain and a cytoplasmic tail [2,3]. The mucin stalks serve to tether the chemokines to the cell membrane, while soluble versions of CXCL16 can be released by the action of membrane metalloproteinases [4,5].…”
Section: Introductionmentioning
confidence: 99%